1998
DOI: 10.1088/0957-0233/9/3/026
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of thermophysical properties by thermal impedance measurements taken under random stimuli taking sensor-induced disturbance into account

Abstract: The characterization of thermal systems can be performed by using thermal impedance measurements. Experimentally, this method requires simultaneous measurements of the variations in heat flux and the temperature of the measuring surface. The sensor, placed on the system to be characterized, induces a disturbance. For a slow change in thermal characteristics and for low frequencies, the disturbance due to the sensor is negligible. The low-frequency case has been studied in several works, but we show here that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The flux density and temperature are measured for a single isothermal surface. If a relationship between the thermal units at the output of the kind θ o = Z o φ o is known, we can then write the relationship [34] in the following way: We can therefore define the input thermal impedance as follows:…”
Section: Quadrupoles and Thermal Impedancementioning
confidence: 99%
See 1 more Smart Citation
“…The flux density and temperature are measured for a single isothermal surface. If a relationship between the thermal units at the output of the kind θ o = Z o φ o is known, we can then write the relationship [34] in the following way: We can therefore define the input thermal impedance as follows:…”
Section: Quadrupoles and Thermal Impedancementioning
confidence: 99%
“…The contact resistance between the probe and the material is integrated in the physical model. Previous studies have shown that it could be identified in every test carried out [34].…”
mentioning
confidence: 94%
“…Thermal impedance [5] is defined in the Laplace domain as the ratio of the temperature and heat flux Laplace transforms. Thus, Z ( p) can be written as…”
Section: Experimental Setup and Thermal Impedance Modelingmentioning
confidence: 99%
“…7). PRBS [12] are signals easily generated by way of a series of high and low levels defined by deterministic laws; their statistical properties can be simulated as, and can be shown to be equivalent to, random processes [5]. Their spectrum is very rich as a frequency range, the upper limit depending on the rate of change of state and on the maximum number of bits included in the PRBS.…”
Section: Model Validation Stagementioning
confidence: 99%
“…This impedance function is also an analogy with electrical or mechanical systems (Defer et al, 1998). Their values are found by the application of the Fast Fourier transform of the data x(t) and y(t).…”
Section: Dynamical Systemmentioning
confidence: 99%